Iron ion elution body

The use of a molded carrier core with metal iron, toner, and carbon material addresses the instability of iron ion elution, ensuring efficient and long-term distribution and purification of water by forming partial batteries, thus improving water quality and reducing environmental impact.

JP2025011347APending Publication Date: 2025-01-24SHARP KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023113375
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing iron ion elution methods using iron powder with large particle diameters and low surface area result in insufficient distribution and unstable elution of iron ions, leading to ineffective water purification.

Method used

A carrier core containing metal iron with a toner and carbon material, molded by pressing, which facilitates sufficient distribution and long-term stable elution of iron ions by forming partial batteries with carbon.

Benefits of technology

The solution enables efficient and stable elution of iron ions, improving water purification by reducing environmental impact and enhancing water quality through reactions with pollutants like hydrogen sulfide and nutrients, preventing odors and promoting photosynthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011347000001_ABST
    Figure 2025011347000001_ABST
Patent Text Reader

Abstract

To provide an iron ion elution body for sufficiently dispersing iron ions in water so as to be able to elute a stable amount of iron ions for a long-term.SOLUTION: An iron ion elution body includes: developers which have carrier cores containing metallic iron and toners adhering to parts of surfaces of the carrier cores; and a carbon material covering the developers. The iron ion elution body is a molded body formed by pressing the developers and the carbon material.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an iron ion eluent. [Background technology]

[0002] Eluting bodies have been disclosed in the past.

[0003] For example, Patent Document 1 discloses an iron ion eluent made by mixing and sintering iron powder and coke powder (carbon). In the iron ion eluent, electrons move from iron to carbon, turning the iron into a divalent ion, which releases iron ions into water and binds with phosphorus and nitric acid, which are causes of eutrophication, to purify the water. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-053304 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the iron ion eluent disclosed in the above-mentioned document uses iron powder, which has a large particle diameter and a small contact area between the iron and carbon, and therefore cannot be sufficiently dispersed. Therefore, unless a large amount of the iron powder is added to water, water purification cannot be achieved, and there is a problem that a stable amount of iron ions cannot be eluted over the long term.

[0006] In view of the above problems, the present disclosure provides an iron ion eluter that can sufficiently disperse iron ions in water and elute a stable amount of iron ions over the long term. [Means for solving the problem]

[0007] An iron ion elution body according to one aspect of the present disclosure is characterized in that it comprises a developer including a carrier core containing metallic iron and a toner adhering to a portion of a surface of the carrier core, and a carbon material coating the developer, and is a molded body formed by pressing the developer and the carbon material together. Effect of the Invention

[0008] As described above, according to the present disclosure, it is possible to provide an iron ion eluter that can sufficiently disperse iron ions in water and elute a stable amount of iron ions over the long term. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a cross-sectional view of an iron ion eluent according to the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view of a developer provided with an iron ion eluting material according to the present disclosure. [Diagram 3] FIG. 3 is a cross-sectional view of a carrier provided in an iron ion eluting body according to the present disclosure. [Figure 4] FIG. 4 is a diagram showing the iron ion eluent according to the present disclosure formed into a pellet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, preferred embodiments of the present disclosure will be described in detail with reference to the drawings. Note that the embodiments described below do not unduly limit the contents of the present disclosure described in the claims, and all of the configurations described in the embodiments are not necessarily essential as the means for solving the problems of the present disclosure.

[0011] Fig. 1 is a cross-sectional view of an iron ion eluting body 100 according to the present disclosure. As shown in Fig. 1, the iron ion eluting body 100 according to the present disclosure includes a developer 10 and a carbon material 20. The iron ion eluting body 100 according to the present disclosure is a molded body formed by pressing the developer 10 and the carbon material 20. The iron ion eluting body 100 is a molded body, not a sintered body. The iron ion eluting body 100 according to the present disclosure is a molded body formed by pressing without applying heat.

[0012] The developer 10 and the carbon material 20 will be described below.

[0013] 1, the carbon material 20 covers the developer 10. The carbon material 20 may cover the entire surface of the developer 10. When the carbon material 20 is in contact with the developer 10, a local battery is generated and iron ions are eluted.

[0014] The carbon material 20 is also used as a binder for pressing the developer 10 to form a molded body. For example, coke, charcoal, coal powder, graphite, coal tar pitch, carbon black, acetylene black, activated carbon, graphite, porous carbon materials, etc. can be used as the carbon material 20. These materials can be used alone or in combination of two or more. The shape and particle size of the carbon material are not important, but a powder is preferred in order to increase the number of contact points with the carrier core, and a particle size smaller than that of the carrier is preferred. Among these, the smaller the particle size, the greater the surface area and the greater the number of contact points with the carrier core, so a particle size of 500 μm or less is preferred, and 50 μm or less is more preferred.

[0015] 2 is a cross-sectional view of a developer 10 provided in the iron ion eluting material 100 according to the present disclosure. As shown in FIG. 2, the developer 10 includes a carrier core 11 containing metallic iron and a toner 12 adhering to a part of the surface of the carrier core 11. The toner 12 also functions as a binder for the iron ion eluting material 100.

[0016] The developer 10 is used for printing by a printer or the like, and may be either pre-used or post-used.

[0017] Since the iron ion eluting body 100 includes the carrier core 11 containing metallic iron, the carrier core 11 and the carbon material 20 that come into contact with each other in water react with each other to generate divalent iron ions.

[0018] Moreover, the developer 10 has a small particle size of 100 μm or less and a large surface area. Also, there are many contact points between the iron contained in the carrier core 11 and the carbon contained in the carbon material 20 and the toner 12. Therefore, the iron ion eluting body 100 including the developer 10 can disperse iron ions sufficiently in water and elute a stable amount of iron ions over a long period of time. Furthermore, the iron ion eluting body 100 according to the present disclosure does not require sintering, so the environmental burden associated with its production can be reduced.

[0019] The carrier core 11 and the toner 12 contained in the developer 10 will be described in detail below.

[0020] The carrier core 11 contains metallic iron. Metallic iron is distinguished from iron oxide, such as ferrite. The shape of the carrier core 11 can range from irregular to spherical. The average particle size of the carrier core 11 can be 10 μm or more and 150 μm or less, and more preferably 30 μm or more and 100 μm or less. The iron particles can be publicly known, and examples of such particles include reduced iron particles, atomized iron particles, and iron nitride particles. Since the reduced iron particles and iron nitride particles are irregular, they may be subjected to a spheroidizing treatment.

[0021] The toner 12 adheres to and connects to a part of the surface of the carrier core 11 or the carrier coating material 13. The toner 12 is preferably contained in the developer 10 at 3 to 10 wt %, more preferably at 5 to 9 wt %. By setting the concentration within this range, the toner 12 functions as a binder for the iron ion eluting material 100, and the toner 12 is less likely to crumble even when placed in water.

[0022] The carrier coating agent 13 preferably contains carbon and carbon black. The amount of carbon black contained in the carrier coating agent 13 is preferably 5 to 10 wt %. In this way, the carbon contained in the coating agent acts as a conductive agent to conduct electrons generated when iron ions are generated, and the carbon of the carrier coating agent 13 can also store electrons. In addition, since the toner 12 also serves as a binder, the toner 12 and the carrier coating agent 13 contain carbon, which makes it possible to conduct electrons throughout the iron ion eluting body 100, and when the toner 12 and the carrier coating agent 13 are put into water, the toner 12 and the carrier coating agent 13 can sink and release the accumulated electrons into the ground. Even if electrons can be stored, they will remain unless there is a means to release them outside the system of the iron ion eluting body 100, so it is possible to elute iron ions for a longer period of time.

[0023] In this way, the carrier core 11 contains metallic iron, and the carbon material 20, carrier coating agent 13, and toner 12 contain carbon, so that when placed in water, a battery reaction occurs locally due to the difference in electronegativity between iron and carbon (Fe: 1.8, C: 2.5), and iron electrons move to carbon to generate divalent iron ions. In other words, the iron ion eluter according to the present disclosure includes toner in addition to the carrier core containing metallic iron, and can thus elute a stable amount of iron ions over the long term.

[0024] The toner 12 includes toner base particles and an external additive.

[0025] The toner base particles contain a binder resin, a colorant, and a release agent. In addition, a charge control agent, a wax dispersant, a grinding aid, etc. may be contained as necessary. The volume average particle size of the toner base particles is not particularly limited, but can be appropriately selected depending on the purpose. It is preferably 4 to 8 μm. The particle size distribution of the toner base particles is not particularly limited, but can be appropriately selected depending on the purpose, and it is preferable that particles of 3 μm or less are 40% by number or less. The circularity of the toner base particles is not particularly limited, but can be appropriately selected depending on the purpose, and it is preferably 0.92 to 0.97. The glass transition point (Tg) of the toner base particles is preferably 60° C. or less.

[0026] The binder resin may be a resin commonly used in the art. A combination of a plurality of resins may be used. The glass transition point (Tg) of the binder resin is preferably 40°C or higher and lower than 70°C.

[0027] The colorant may be a carbon-based coloring material, such as carbon black, acetylene black, activated carbon, graphite, porous carbon material, etc. The amount of the colorant is preferably 5 to 10 parts by weight, more preferably 7 to 10 parts by weight, based on 100 parts by weight of the resin.

[0028] The release agent may be a release agent commonly used in the art. A combination of a plurality of release agents may be used. The melting point of the release agent is preferably 70°C or higher and lower than 150°C. The amount of the release agent to be added may be appropriately selected depending on the purpose. The amount is preferably 0.5 to 5.0 parts by weight, more preferably 2.0 to 5.0% by weight, based on 100 parts by weight of the resin.

[0029] The charge control agent may be a charge control agent commonly used in the art. The amount of the charge control agent may be appropriately selected depending on the purpose. The amount is preferably 0.5 to 3 parts by weight per 100 parts by weight of the resin. In terms of weight percent, the amount is preferably 0.5 to 2.0% by weight.

[0030] As the wax dispersant, any wax dispersant commonly used in the art can be used.

[0031] The grinding aid may be a wax dispersant commonly used in the art.

[0032] As the external additive, an external additive commonly used in the technical field can be used.

[0033] 3 is a cross-sectional view of the carrier 14 included in the iron ion eluting material 100 according to the present disclosure. As shown in FIG. 3, the carrier 14 includes a carrier core 11 and a carrier coating agent 13 that covers a part of the carrier core 11.

[0034] The particle size of the carrier 14 in the developer 10 is preferably 20 to 100 μm in D50, and (D90-D10) / D50 is preferably 0.5 to 2.0, more preferably 0.8 to 1.3. The particle size distribution of the developer 10 is sharp and uniform. In this way, the number of contact points for forming a local battery between the metallic iron of the carrier core 11 and the carbon material 20 or the carbon of the toner 12 increases, and the efficiency of iron ion elution increases. In addition, the improved mixability allows the carbon material 20 to be mixed uniformly. On the other hand, if the particle size is large, the number of contact points between the metallic iron and carbon decreases, and if the particle size is small, the mixability with the carbon material 20 deteriorates due to a decrease in bulk density, and it is considered that voids are generated in the iron ion eluting body 100 due to the elution of iron, making it easy to collapse.

[0035] The ratio of the developer 10 to the carbon material 20 is preferably 3:7 to 9:1, and more preferably 7:3 to 9:1. This increases the number of contact points between the metallic iron contained in the carrier core 11 of the developer 10 and the carbon material 20, thereby improving the efficiency of iron ion elution.

[0036] The developer 10 preferably further comprises a carrier coating agent 13 that covers a portion of the carrier cores 11 and the toner 12. By covering a portion of the area where the water and metallic iron are in contact with each other with the carrier coating agent 13, it is possible to prevent the iron ion eluting body 100 from corroding. Furthermore, although the carrier cores 11 become smaller due to the elution of iron ions, the carrier coating agent 13 allows the carrier cores 11 to maintain their shape, making them less likely to crumble even when left in water for a long period of time.

[0037] The carrier coating agent 13 preferably contains carbon and carbon black. The carbon and carbon black contained in the carrier coating agent 13 act as a conductive agent for electrons generated when iron ions are generated, and the electrons can be stored in the carbon in the carrier coating agent 13. If electrons remain near the contact point between iron and carbon, they may hinder the elution of iron ions. Therefore, by doing this, a stable amount of iron ions can be eluted over a longer period of time.

[0038] The carrier coating agent 13 is preferably contained in the carrier 14 at 0.5 to 5.0 wt %, and more preferably at 0.5 to 3.0 wt %. In this way, electrons can be appropriately stored in the carbon in the carrier coating agent 13, and a stable amount of iron ions can be eluted over a longer period of time.

[0039] The coverage of the carrier cores 11 with the carrier coating agent 13 is preferably 30 to 90%, and more preferably 60 to 80%. In this way, the carrier coating agent 13 peels off to a certain extent from the carrier cores 11, exposing the metallic iron of the carrier cores 11, improving the contact between the carbon material 20 and the carrier cores 11, and improving the efficiency of elution of iron ions. Note that when the developer 10 including the carrier coating agent 13 is used after printing with a printer or the like, the coverage of the carrier coating agent 13 covering the carrier cores 11 decreases.

[0040] As mentioned above, the developer 10 may be either unused or used, but it is preferable to use used developer 10 where the coverage rate is reduced (coverage rate of 90% or less). In this way, the developer 10 is used in a printer or the like, and if the used developer 10 is reused as an iron ion eluent, it will lead to a reduction in the environmental load.

[0041] 4 is a diagram showing the iron ion eluting material according to the present disclosure molded into a pellet shape. The iron ion eluting material 100 according to the present disclosure may be molded into a pellet shape as shown in FIG.

[0042] The effect of the iron ion eluting material 100 according to the present disclosure will be described.

[0043] First, the iron ion eluting body 100 according to the present disclosure is submerged in water, and iron ions are eluted.

[0044] The iron ions then react with the surrounding substances. For example, iron ions react with hydrogen sulfide (H2S), which causes bad odors in sludge, and with phosphoric acid from eutrophic detergents, pesticides, fertilizers, etc. This allows the foul-smelling hydrogen sulfide (H2S) and eutrophic phosphoric acid to be removed from the water. The resulting substances precipitate as iron sulfide and iron phosphate.

[0045] In this way, the iron ion eluting body 100 according to the present disclosure can prevent eutrophication and foul odors such as sludge that cause blue-green algae and red tides, and can purify and improve water quality. Furthermore, the iron is absorbed by plants P in the water, which activates photosynthesis and increases the oxygen concentration in the water, improving the environment. EXAMPLES

[0046] The iron ion eluent according to the present disclosure will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the examples described here.

[0047] Example 1 (Carrier core manufacturing) Silicone resin (KR-255, Shin-Etsu Chemical Co., Ltd.) was used, and carbon black (Ketjen Black EC, Lion Corporation) was added to a concentration of 5.0% by weight, which was then dispersed in toluene to prepare a dispersion. The obtained dispersion was applied to iron particles having a particle diameter of 60 μm using a fluidized bed type coating device, and the applied coating resin was cured by heating at 250° C. for 2 hours to obtain a carrier core partially coated with a carrier coating agent.

[0048] (Toner manufacturing) Next, the raw materials, which were a binder resin (89% by mass of polyester resin), a colorant (8% by mass of carbon black (manufactured by Mitsubishi Chemical Corporation, product name: MA-77)), a release agent (2% by mass of paraffin wax (melting point 90°C, manufactured by Nippon Seiro Co., Ltd., product name: Fischer-Tropsch wax FNP0090)), and a charge control agent (1% by mass of potassium salt (bis[benzilate(2-)-κ(2)O,O]borate(1-) potassium, solubility in water 4.382 g / L (20°C), manufactured by Nippon Carlit Co., Ltd., product name: ion conductive material LR-147)) were premixed for 5 minutes at a rotation speed of 1500 rpm using a high-performance fluid mixer (Henschel mixer, total capacity: 20 L, manufactured by Mitsui Mining Co., Ltd. (now Nippon Coke and Engineering Co., Ltd.), model: FM20C).

[0049] The obtained mixture was melt-kneaded using a twin-screw extruder (manufactured by Ikegai Corporation, model: PCM-30) under conditions of a cylinder set temperature of 100°C, a barrel rotation speed of 250 rpm, and a raw material supply rate of 10 kg / hour to obtain a melt-kneaded product.

[0050] The obtained molten kneaded material was cooled and solidified using a cooling belt, and then the solidified material was finely pulverized using a fluidized bed opposed jet mill (manufactured by Hosokawa Micron Corporation, model: Counter Jet Mill AFG) and classified (particle size adjustment) using a rotary (centrifugal airflow) classifier (manufactured by Hosokawa Micron Corporation, model: TSP Separator) to obtain toner particles (toner cores) with a volume average particle size of 5.0 μm to 7.0 μm.

[0051] To 1000 g of the obtained toner particles, 10 g of commercially available silica fine particles (manufactured by Nippon Aerosil Co., Ltd., product name: R976s) and 3 g of silica-doped strontium titanate (fine powder in which the surface of a composition containing strontium titanate and silica has been hydrophobized with a silane compound, average primary particle diameter: 20 μm) were added as external additives, and the mixture was mixed for 3 minutes at a rotation speed of 3500 rpm using a high-performance fluidized mixer (Henschel mixer, total capacity: 20 L, manufactured by Mitsui Mining Co., Ltd. (now Nippon Coke and Engineering Co., Ltd.), model: FM20C) to obtain 1 kg of toner.

[0052] (Manufacture of developer) The toner obtained by the above manufacturing method and the carrier core were weighed out so that the toner concentration was 7.0% (toner / carrier = 1 / 13.3), and the mixture was stirred and mixed for 20 minutes in a V-type mixer (manufactured by Tokuju Machinery Co., Ltd., model: V-5) to obtain a two-component developer.

[0053] The above two-component developer was filled into the developing unit of a commercially available copier, and 100,000 sheets of A4 recording paper with a print rate of 5% were printed. After that, the two-component developer was removed from the developing tank, and the coverage rate of the carrier coating agent was measured. The coverage rate of the carrier core covered by the carrier coating agent was found to be 70%.

[0054] The average particle size of the developer was 60 μm in D50, (D90-D10) / D50 was 1.3, the toner concentration was 7 wt%, and the carbon black in the toner was 8 wt%.

[0055] (Method of manufacturing iron ion eluent) The manufacturing method for the iron ion eluate was to measure the two-component developer and carbon material (carbon black (product name: MA-77, manufactured by Mitsubishi Chemical Corporation)) after printing at a ratio of 3:1 (7.5 g of two-component developer, 2.5 g of carbon material), place them in a wide-mouth bottle (50 mL, Aiboy PP wide-mouth bottle, manufactured by AS ONE Corporation), and mix them on a double-axis driven plastic bottle rotating table (Tanaka Tech Co., Ltd., model: RPB-3S). The mixed sample was molded into cylindrical pellets with a diameter of 25φ (φ25 carbide die, 30 MPa, 1 minute) using a 50kN table press TB-50H manufactured by NPa Systems Co., Ltd.

[0056] In this manner, the iron ion eluent of Example 1 was obtained.

[0057] Example 2 In Example 2, the average particle size of the developer was set to 17 μm in terms of D50, and the other conditions were the same as those in Example 1 to obtain an iron ion eluate according to the example.

[0058] Example 3 In Example 3, the average particle size of the developer was set to 20 μm in terms of D50, and the other conditions were the same as those in Example 1 to obtain an iron ion eluate according to the example.

[0059] Example 4 In Example 4, the average particle size of the developer was set to 100 μm in terms of D50, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the example.

[0060] Example 5 In Example 5, the average particle size of the developer was set to 105 μm in terms of D50, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the example.

[0061] Example 6 In Example 6, the average particle size of the developer was set to 55 μm in terms of D50, and (D90−D10) / D50 was set to 0.4, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the example.

[0062] Example 7 In Example 7, an iron ion eluate according to the present invention was obtained under the same conditions as in Example 1, except that the average particle size of the developer was set to 56 μm in terms of D50 and (D90−D10) / D50 was set to 0.5.

[0063] Example 8 In Example 8, an iron ion eluate according to the present example was obtained under the same conditions as in Example 1, except that the average particle size of the developer was set to 62 μm in terms of D50 and (D90−D10) / D50 was set to 2.0.

[0064] Example 9 In Example 9, the average particle size of the developer was set to 64 μm in terms of D50, and (D90−D10) / D50 was set to 2.1, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the example.

[0065] Example 10 In Example 10, the average particle size of the developer was set to 59 μm in D50, (D90-D10) / D50 was set to 1.4, and no carrier coating agent was added. Otherwise, an iron ion eluate of the example was obtained under the same conditions as in Example 1.

[0066] Example 11 In Example 11, an iron ion eluate according to the present example was obtained under the same conditions as in Example 1, except that the average particle size of the developer was 58 μm in D50 and the coverage of the carrier coating agent was 28%.

[0067] Example 12 In Example 12, an iron ion eluate according to the present example was obtained under the same conditions as in Example 1, except that the average particle size of the developer was 58 μm in D50 and the coverage of the carrier coating agent was 30%.

[0068] (Example 13) In Example 13, the coverage rate of the carrier coating agent was set to 90%, and the other conditions were the same as those of Example 1 to obtain an iron ion eluent according to the example.

[0069] Example 14 In Example 14, the coverage rate of the carrier coating agent was set to 93%, and the other conditions were the same as those of Example 1 to obtain an iron ion eluent according to the example.

[0070] Example 15 In Example 15, the carbon black in the carrier coating agent was omitted, and the other conditions were the same as those in Example 1 to obtain an iron ion eluent according to the example.

[0071] (Example 16) In Example 16, the toner concentration in the developer was set to 2.8 wt %, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the example.

[0072] (Example 17) In Example 17, the toner concentration in the developer was set to 3.0 wt %, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the example.

[0073] (Example 18) In Example 18, the toner concentration in the developer was set to 10.0 wt %, and the other conditions were the same as those in Example 1 to obtain an iron ion eluate according to the example.

[0074] (Example 19) In Example 19, the toner concentration in the developer was set to 10.5 wt %, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the example.

[0075] (Example 20) In Example 20, the concentration of carbon black in the toner was set to 4.8 wt %, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the present example.

[0076] Example 21 In Example 21, the concentration of carbon black in the toner was set to 5.0 wt %, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the present example.

[0077] Example 22 In Example 22, the concentration of carbon black in the toner was set to 10.0 wt %, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the present example.

[0078] (Example 23) In Example 23, the concentration of carbon black in the toner was set to 10.2 wt %, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the present example.

[0079] (Example 24) In Example 24, an iron ion eluate according to the present invention was obtained under the same conditions as in Example 1, except that the ratio of the developer to the carbon material was 1.0:4.0.

[0080] (Example 25) In Example 25, the ratio of the developer to the carbon material was set to 3.0:7.0, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the present example.

[0081] (Example 26) In Example 26, the ratio of the developer to the carbon material was set to 9.0:1.0, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the present example.

[0082] Example 27 In Example 27, the ratio of the developer to the carbon material was set to 9.5:0.5, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the present example.

[0083] Comparative Example 1 In Comparative Example 1, ferrite that is a sintered body to which heat is applied, rather than a molded body molded by pressing, was used to obtain an iron ion elution body according to the Comparative Example.

[0084] Comparative Example 2 In Comparative Example 2, a developer was produced in the same manner as in Example 1, and was only mixed with a carbon material to obtain an iron ion elution body according to the Comparative Example that was not press molded (not a molded body).

[0085] Comparative Example 3 In Comparative Example 3, no carbon material was added, and the other conditions were the same as those of Example 1 to obtain an iron ion eluate according to the comparative example.

[0086] With regard to the particle diameter, (D90-D10) / D50, the average particle diameter D50, and D90 and D10 were measured using a Microtrack particle size analyzer (manufactured by Nikkiso Co., Ltd.).

[0087] The amount of carrier coating agent was confirmed using a calorimeter measuring device (TGA) to see if a mass loss occurred when the temperature was raised from room temperature to 800°C at a heating rate of 10°C / min in a nitrogen atmosphere. Separation from the toner in the developer was confirmed using a TREK JAPAN model 210HS-2A. 0.2g of developer was taken and placed on a stand, and covered with a stainless steel mesh (#795). Next, a suction nozzle was placed on the mesh, and the toner in the developer was sucked and separated.

[0088] The coverage rate of the carrier core with the carrier coating agent was calculated using the following method. First, a scanning electron microscope (SEM) was used to observe the surface of the developer with the carrier coating agent with an electron beam at an acceleration voltage of 2.0 kV without depositing a conductive material such as gold on the surface. Since the carrier core (metallic iron) is observed as white, the ratio of the area of ​​the other parts to the total area of ​​the developer was calculated. This was performed for 100 carrier particles, and the average of the obtained values ​​was taken as the coating coverage rate.

[0089] The presence or absence of carbon black in the carrier coating agent was determined using a thermogravimetric analyzer (TGA). The sample was heated in a nitrogen atmosphere from 40°C to 600°C at 20°C / min, and then held for 5 minutes. Here, organic matter other than CB (carbon black) was decomposed. It was then cooled to 400°C at 20°C / min, the atmosphere was changed from nitrogen to air, and held for 5 minutes, after which it was heated to 800°C at 20°C / min, and held for 30 minutes. If there was a weight loss rate after changing from a nitrogen atmosphere to an air atmosphere, it contained carbon material (carbon black).

[0090] The toner concentration in the developer was confirmed using a TREK JAPAN model 210HS-2A. 0.2g of developer was taken and placed on a stand, and covered with a stainless steel mesh (#795). Next, a suction nozzle was placed on the mesh to suck up the toner in the developer. The weight of the developer remaining on the stand was then measured, and the toner concentration was measured.

[0091] The carbon black concentration in the toner was calculated by measuring the toner sucked in when measuring the toner concentration in the developer using a TGA. The sample was heated in a nitrogen atmosphere from 40°C to 600°C at 20°C / min, and then held for 5 minutes. Here, organic matter other than CB (carbon black) is decomposed. It was then cooled to 400°C at 20°C / min, the atmosphere was changed from nitrogen to air, and held for 5 minutes, after which it was heated to 800°C at 20°C / min and held for 30 minutes. The weight loss rate after changing from a nitrogen atmosphere to an air atmosphere was taken as the amount of carbon black.

[0092] The particle size of the developer and the composition of the iron ion eluate are shown in the table below.

[0093] [Table 1A]

[0094] [Table 1B]

[0095] The iron ion eluting bodies according to the above examples and comparative examples were immersed in water, and the Fe in the water was measured after 3 days and 10 days. 2+ The concentration of Fe was measured. 2+ The concentration was measured as follows: Distilled water was placed in a glass sample bottle in an amount 20 times the weight of the prepared iron ion eluate (100 g of distilled water for a 5 g sample), and after leaving it for 3 days and 10 days, the divalent iron ion concentration of the supernatant liquid in the water was measured using a Pack Test (Kyoritsu Chemical Research Institute, Ltd.).

[0096] The appearance of the molded bodies after the iron ion eluting materials according to the above examples and comparative examples were observed immediately after the impregnation and after 10 days. The appearance was evaluated as follows. ◎: Exists in the shape it was molded in (very good) 〇: Partially collapsed (Excellent) △: It has crumbled, but the molded body is still barely intact (slightly superior) ×: The molded shape is not retained (almost powdered) (not excellent)

[0097] The above evaluation results are shown in the table below.

[0098] [Table 2]

[0099] In all examples, Fe was detected after 3 and 10 days. 2+The concentration was 0.1 ppm or more, and iron ions were dissolved and dispersed sufficiently in water. In particular, in the iron ion-eluting body in which the coverage rate of the carrier core with the carrier coating agent was low, Fe 2+ The results were excellent. The iron ion eluate showed a tendency to elute a large amount of Fe even in the iron ion eluate with a small particle size, a low toner concentration, and a high developer ratio. 2+ The results showed a tendency to elute more of the compound, which was excellent.

[0100] In addition, in all the examples, the appearance retained the shape at the time of molding immediately after impregnation and after 10 days, showing excellent results. Among them, the iron ion eluted body in which the carrier core was covered with a high coverage rate of the carrier coating agent showed excellent results, such as remaining in the shape as it was molded. Furthermore, the iron ion eluted body with a high toner concentration, the iron ion eluted body with a low concentration of carbon black in the toner, and the iron ion eluted body with a high ratio of carbon material also showed excellent results.

[0101] On the other hand, in Comparative Example 1 using ferrite, Comparative Example 2 not molding, and Comparative Example 3 not adding a carbon material, Fe 2+ The amount of elution was extremely small, resulting in poor results. Furthermore, except for Comparative Example 1, the results of the appearance after impregnation were also poor.

[0102] As described above, the iron ion eluent according to the present disclosure can disperse iron ions sufficiently in water and can elute a stable amount of iron ions over the long term.

[0103] Although each embodiment and each example of the present disclosure have been described in detail above, it will be readily apparent to those skilled in the art that many modifications are possible without substantially departing from the novel features and effects of the present disclosure. Therefore, all such modifications are intended to be included within the scope of the present disclosure.

[0104] For example, a term described at least once in the specification or drawings together with a different term having a broader or similar meaning can be replaced with that different term anywhere in the specification or drawings. In addition, the configuration and operation of the iron ion eluting body are not limited to those described in the embodiments and examples of the present disclosure, and various modifications are possible. [Explanation of symbols]

[0105] 10 developer, 11 carrier core, 12 toner, 13 carrier coating agent, 14 carrier, 20 Carbon materials, 100 Iron ion elution body, P plant

Claims

1. a developer comprising a carrier core containing metallic iron and a toner adhering to a portion of a surface of the carrier core; a carbon material that coats the developer; Equipped with An iron ion elution body, which is a molded body obtained by pressing the developer and the carbon material together.

2. The iron ion eluent according to claim 1 , wherein the developer further comprises a carrier coating agent that covers the carrier core and a part of the toner.

3. the developer further comprises a carrier including the carrier core and a carrier coating agent that covers a portion of the carrier core; 2. The iron ion eluent according to claim 1, characterized in that the particle size of the carrier is 20 to 100 μm in terms of D50, and (D90-D10) / D50 is 0.5 to 2.

0.

4. 2. The iron ion eluate according to claim 1, wherein the toner is contained in the developer at 3 to 10 wt %.

5. 2. The iron ion eluent according to claim 1, wherein a ratio of the developer to the carbon material is 3:7 to 9:

1.

6. 3. The iron ion eluent according to claim 2, wherein the carrier coating agent contains carbon black.

7. The toner contains carbon black, 2. The iron ion eluate according to claim 1, wherein the carbon black contained in the toner is contained in the developer at 5 to 10 wt %.

8. 3. The iron ion eluent according to claim 2, wherein the carrier core is covered with the carrier coating agent at a coverage rate of 30 to 90%.

Citation Information

Patent Citations

  • Sintered compact and method for producing the same

    JP2018053304A